Quantitative study on carbon emissions of modified recycled asphalt mixture based on life cycle assessment method - Xiaohua Liu; Lu Deng; Henglong Zhang; Jiangmiao Yu (Developments in the Built Environment)
The recycled asphalt technology is considered to have environmental sustainability prospects due to the resource conservation of old material recycling. Nonetheless, how to quantitatively evaluate the environmental impact of the entire life cycle of recycled asphalt pavement (RAP) still needs to be sorted out. Based on the theory of life cycle management, through the Life-cycle assessment (LCA) method, this study establishes a quantitative assessment model for the environmental impact of recycled asphalt pavement. A quantitative assessment model is established for the full life cycle environmental impact of recycled asphalt pavement. The model can output a list of environmental impacts for each stage of the life cycle, and can also conduct characteristic impact assessments based on five major impact categories: energy consumption (EC), global warming potential (GWP), acidification potential (AP), human health hazards (HTP), and particulate matter emissions. The results indicate that the acquisition of raw materials is the dominant stage for the environmental impact of cold recycled asphalt pavement, with a proportion of over 50% for each major impact category. In the construction of highways, using recycled modified asphalt mixture can reduce the total emissions by 12,976 kg per kilometer. In addition, the life cycle inventory (LCI) analysis shows that the environmental impact of recycled asphalt pavement is mainly quantified by energy consumption and various pollutant emissions, such as CO2, CH4, SO2, CO, N2O, NMVOC, particulate matter, and asphalt smoke. The raw material extraction stage has been identified as the stage with the greatest environmental impact, making significant contributions in energy consumption, global warming potential, acidification potential, human health hazards, and particulate matter emissions. This indicates that utilizing cold recycling technology and increasing the use of recycled RAP materials are efficient ways to promote energy conservation, reduce emissions, and minimize the environmental impact of asphalt pavement throughout its lifecycle.